Return Mode Selection and Pricing Strategy for a Dual-Channel Retailer - Xiaojian Hu; Shuai Feng; Jiqiong Liu; Aifeng Yang; Guanxiong Wang; Hui Xu (Discrete Dynamics in Nature and Society)
With the rapid development of e-commerce and the economy, an increasing number of retailers are adopting a dual-channel retail strategy (DCRS), which allows customers to return unsatisfactory products, provided that their complaints are reasonable, and receive a full refund. This paper studies the pricing strategies of an integrated dual-channel retailer (DCR) when it provides return policies to customers, including original channel return, fixed cross-channel return, and relaxed cross-channel return. The relationship between the DCR’s system performance and channel pricing is impacted by customer channel preferences, and the return rates of different channels are discussed. The results show that the greater the difference in customer preferences between channels is, the greater the profitability of the DCR will be. A fixed cross-channel return model should be selected when the return rate in the online channel is higher or the cross-channel return rate is lower; otherwise, the original channel return model should be selected. When the return rate of a certain channel is high, the retailer should increase the price in that channel and reduce the pricing of its competing channel to compensate for the loss caused by the returns and transfer sales between channels. A selective return policy can not only improve the flexibility of business operations and enhance competitive advantage but also provide convenient customer returns and enhance consumers’ sense of security.